Lipopolysaccharide-Induced Memory Impairment in Rats: a Model of Alzheimer’s Disease - R., Zakaria; W. M. H., Wan Yaacob; Z., Othman; I. , Long; A. H. , Ahmad; B. , Al-Rahbi (Akademie Ved Ceske Republiky, 2017)
Alzheimer’s disease (AD) is a primary cause of dementia in the middle-aged and elderly worldwide. Animal models for AD are widely used to study the disease mechanisms as well as to test potential therapeutic agents for disease modification. Among the non-genetically manipulated neuroinflammation models for AD, lipopolysaccharide (LPS)-induced animal model is commonly used. This review paper aims to discuss the possible factors that influence rats’ response following LPS injection. Factors such as dose of LPS, route of administration, nature and duration of exposure as well as age and gender of animal used should be taken into account when designing a study using LPS-induced memory impairment as model for AD.